Infantile cortical hyperostosis - Ramírez Suárez, Reynier; López Consuegra, Yuslaidy A.; Peña Reyes, Rachel (Revista Argentina de Cirugía, 2026)
Infantile cortical hyperostosis (ICH) or Caffey disease is a self-limiting bone disorder characterized by fever, irritability, soft tissue swelling and cortical bone thickening. It is more common in infants < 6 months of age. We report the case of a 3-month-old infant with the clinical and radiographic characteristics of the disease and the most common laboratory findings which enabled an accurate diagnosis and appropriate management. The acute episode persisted for several days, followed by a complete resolution of the edema within four weeks. Identifying this rare infection will help avoid invasive diagnostic and therapeutic strategies.